Personaleinsatzplanung in der operativen Anästhesie: Strukturierte Interviews mit 23 personalverantwortlichen Oberärzten = Human resource planning in operative anaesthesia : Structured interviews with 23 supervising senior physicians - Bent, Franziska; Ahlbrandt, Janko; Weigand, Markus A.; Hofer, Stefan; Lichtenstern, Christoph (Der Anaesthesist, 2016)
BackgroundIn the hospital, human resource planning has to consider the needs and preferences of personnel and planners as well as the financial interest of the hospital. Additionally, staff planning has become more complex due to a growing number of part-time doctors as well as a variety of working shifts.ObjectivesThe aim of the study was to describe existing human resource planning in German anesthesiology departments. Furthermore, we evaluated existing software solutions supporting human resource planning.Materials and methodsAnesthesiology departments of German university hospitals were enrolled in the study. The aspects covered were tools and time needed for planning, amount of conflicts while planning, components of the software solutions and the efficiency and satisfaction according to the users. This was evaluated for short-, intermediate- and long-term planning. Two groups were compared: departments with and without software exchanging information among the three planning periods.ResultsOut of 35 university anesthesiology departments, 23 took part in the survey. On average they employed 105.8 ± 27.8 doctors who had to cover 13.5 ± 6.3 different shifts during a weekday. Personnel planning is mostly done by senior physicians. In some departments, other staff, such as residents and junior doctors, were involved as well. Software that exchanged information between short-, intermediate- and long-term planning was used in 53 % of the departments (12 out of 23). Five departments used commercially available planning software: Polypoint Deutschland (PolypointDeutschland), Atoss (Atoss AG) and SP Expert (Interflex Datensysteme).The time needed for short-term planning was slightly reduced in the exchanging software group. No difference was shown for the intermediate planning period. The use of this software led to a slight reduction in planning conflicts and increased the self-estimated efficiency of the users (p = 0.02).Throughout all groups, the major complaint was missing interfaces, for example between the software and human resources department. The ideal planning software should reduce time needed for planning and prevent planning conflicts according to the interviewed physicians. Furthermore it should be flexible and transparent for all involved staff.ConclusionsThis study analyzed structures established in human resource planning in the anesthesiology departments for the first time. Time for planning varies significantly in comparable departments indicating suboptimal processes. Throughout Germany, the requirements for human resources planning are similar; for example, the software should integrate all aspects of HR planning. Different approaches are under evaluation but so far no software solution has prevailed. The used solutions vary substantially and therefore a comparison is difficult. There is no software solution with wide adoption.
Gesehen am 25.09.2019